Microplastics in agricultural soils following sewage sludge applications: Evidence from a 25-year study - Ramage, Stuart J.F.F.; Coull, Malcolm; Cooper, Patricia; Campbell, Colin D.; Prabhu, Radhakrishna; Yates, Kyari; Dawson, Lorna A.; Devalla, Sandhya; Pagaling, Eulyn (Chemosphere (Oxford), 2025)
Sewage sludges applied to agricultural soils are sources of microplastic pollution, however, little is known about the accumulation, persistence, or degradation of these microplastics over time. This is the first study to provide long-term, high temporal resolution quantitative evidence of microplastics in agricultural soils following sewage sludge application. The abundance and degradation of microplastics was assessed in soils sampled biennially from an experimental field over a 25-year period managed under an improved grassland regime following the application of five different sewage sludges. The sludges contained different microplastic compositions reflecting the different sources of the sludges. Microplastic abundance increased by 723–1445% following sewage sludge applications (p < 0.05) and remained constant over time (22 years and possibly beyond) (p > 0.05). All sludges predominantly added white/transparent microfibres to soil. Microfilms, microfibres, and fragments were most susceptible to degradation, potentially creating micro(nano)plastics. Of note was the discoloration of coloured microfibres, which may be environmentally hazardous due to the toxicity of textile dyes in soil ecosystems. We also found that plastic composition could be used to trace its source. This evidence is useful in informing regulation on sewage sludge use and management, and in assessing the fate and impact of microplastics in soil. [Display omitted] •Application of sewage sludges significantly increased microplastic abundance in soil.•Microplastic abundance remained relatively unchanged over 22 years.•Microfibres and microfilms were susceptible to degradation while other morphologies were resistant.•Textile dyes may have been leached to soil potentially posing further toxic effects.